Assessment of combination therapy in BALB/c mice injected with carbapenem-resistant Enterobacteriaceae strains - Salloum, Noor; Kissoyan, Kohar A.; Cheaito, Katia; Araj, George F.; Hanna Wakim, Rima; Kanj, Souha S.; Kanafani, Zeina A.; Dbaibo, Ghassan; MATAR, GHASSAN M. (Frontiers in Microbiology, 2015)
Monotherapeutic options for carbapenem resistant infections are limited. Studies suggest that combination therapy may be associated with better outcomes than monotherapies. However, this is still controversial. This study assessed, the efficacy of combination therapy against carbapenem resistant Enterobacteriaceae harboring singly various ESBL or carbapenemase encoding genes. Thus, four isolates harboring either blaCTXM-15, blaCTXM-15 and blaOXA-48, blaNDM-1, or blaKPC-2 genes were selected for testing. Minimal Inhibitory Concentration (MIC) was determined by broth dilution method. Gene transcript levels on single and combined treatments were done in vitro and in vivo by q RT-PCR. Assessment of treatments was done in BALB/c mice according to a specific protocol. As such, the qRT-PCR revealed a significant decrease of transcript levels in all isolates upon using rifampicin or tigecycline, singly or in combination with colistin. However, variable levels were obtained using colistin singly or in combination with meropenem or fosfomycin. In vivo assessment showed that all combinations used were effective against isolates harboring blaCTXM-15, blaOXA-48, and blaNDM-1. Conversely, the most significant combination against the isolate harboring blaKPC-2 gene was colistin with carbapenem, fosfomycin, or kanamycin. As a conclusion, combination therapy selected based on the type of carbapenemase produced, appeared to be non-toxic and might be effective in BALB/c mice. Therefore, the use of a rationally optimized combination therapy might lead to better results than monotherapy, however, clinical trials are needed for human consumption.